ANALYSIS OF LETTER AL-BAQARAH VERSE 62 IN STRENGTHENING THE EMERGENCE OF SPIRITUAL SENSES AMONG RELIGIOUS PEOPLE IN INDONESIA VISITED FROM METAPHYSICS - Syarifuddin, Syarifuddin (Proceeding International Seminar of Islamic Studies, 2024)
The Indonesian nation is a pluralistic nation that has various religions, ethnicities and languages. Indonesia's ideology is Pancasila, the first principle reads, "Belief in One Almighty God". Indonesia is officially a presidential and unitary state and not a religious state.Indonesia has a very diverse ethnic composition ranging from race, religion, beliefs, languages, customs, and so on. Each social category has a unique internal culture, so that it is different from other trends, from a cultural and structural perspective this phenomenon reflects a high level of cultural diversity and spiritual level. Differences in spiritual abilities in human life are a definite thing. In the context of religious differences, the concept of religious tolerance is known. Tolerance between religious communities is not just accepting differences but recognizing each other, being open to each other, and understanding each other's differences and not taking issue with these differences. This can be seen in the Koran QS: Albaqarah/2. 62"Indeed, those who believe, the Jews, the Christians and the Shabi'in, whoever (among them) believes in Allah and the Last Day, and does good deeds, they will be rewarded by God- Therefore, there is no fear for them, and they do not grieve.” (Qs. Al-Baqarah/2: 62)Through this metaphysical analysis, if humans, through the potential of their minds and sensory devices which are centered in one unit called the soul, already have spiritual intelligence, they can reach anything that can be seen by human senses (physics) and what cannot be seen by the senses. humans (metaphysics) so that this metaphysical spiritual soul intelligence is able to strengthen intimate relations between religious communities in Indonesia.